Blockchain Revolutionizing Healthcare Industry: A Systematic Review of Blockchain Technology Benefits and Threats. - AbdelSalam, Fatma M. (Perspectives in Health Information Management)
Blockchain technology has been gaining significant traction in the healthcare industry in the past few years. The value proposition of using blockchain technology is to augment interoperability among healthcare organizations. However, the disruptive technology comes with costly drawbacks. The aim of this paper is to explore the benefits and threats of blockchain technology as a disruptive innovation in the healthcare sector. Current blockchain applications were reviewed through studies conducted to identify uses and potential challenges of blockchain technology based on its current implementations. This literature review highlights gaps in research and the need for further blockchain studies, particularly in the healthcare domain.